Wave Based Method for the steady-state vibrations of thick plates. (9th June 2015) - Klanner, M.; Ellermann, K.
Abstract: A commonly used technique for the analysis of the low frequency harmonic response of plates is the Finite Element Method (FEM). Since the computational effort of the FEM increases significantly for higher frequencies, different calculation methods are needed to get accurate results for plate bending problems in the mid and high frequency range. A deterministic method called Wave Based Method (WBM) is able to tackle the mid frequency range due to a higher calculation efficiency. It has already been developed for the Kirchhoff plate theory, which is only accurate for rather thin plates, since shear deformation is neglected. Therefore, in this paper the WBM using a first-order shear deformation theory, the Mindlin plate theory, is developed which makes it applicable to thick plates. Numerical examples with point force excitation are shown.